1986
DOI: 10.2307/3899452
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Practices for Establishing Fourwing Saltbush within Perennial Grass Stands

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Felker et al (1984) showed that various herbicides could control competing herbaceous plant growth and caused a fourfold increase in P. alba dry weight in field plots. Petersen et al (1986) found similar trends for the growth of another woody species. In addition, Bouteloua eriopoda (Torr.)…”
Section: Discussion-supporting
confidence: 61%
See 1 more Smart Citation
“…Felker et al (1984) showed that various herbicides could control competing herbaceous plant growth and caused a fourfold increase in P. alba dry weight in field plots. Petersen et al (1986) found similar trends for the growth of another woody species. In addition, Bouteloua eriopoda (Torr.)…”
Section: Discussion-supporting
confidence: 61%
“…Knoop and Walker (1985) showed that competition with herbaceous plants caused a reduction in both Acacia tortilis and A. nilotica tree growth. Petersen, Ueckert, and Potter(1986) showed in a field study that Atriplex canescens (Pursh) Nutt. (fourwing saltbush) growth was reduced 60-80% when grown in proximity to several grasses.…”
mentioning
confidence: 99%
“…Attributes of the ecotype have been described by Petersen et al (1987). Seedlings were grown from this bulk seed harvest in a greenhouse for 15 weeks, then 1,116 of the seedlings were transplanted into a stand of 'El Reno'sideoats grama in April 1982 (Petersen et al 1986). Growth rates of 511 seedlings that survived were recorded for 38 months after transplanting.…”
Section: Methodsmentioning
confidence: 99%
“…) Torr.] sward in 1982 (Petersen et al 1986). "Superior"phenotypes were >75 cm tall and much-branched after 17 months, whereas "inferior'* phenotypes of the same accession, subjected to the same cultural treatments, were <20 cm tall and sparsely branched.…”
mentioning
confidence: 98%
See 1 more Smart Citation